Interpersonal Antecedents to Selective Disclosure of Lesbian and Gay Identities at Work - Rengers, Julian M. (2021)
Lesbian, gay, and bisexual (LGB) employees’ sexual identitymay be considered a concealable stigmatised identity. Disclosing it to others at work could potentially lead to discrimination and rejection, hence threatening their inclusion. Therefore, they may hide their sexual identity instead, which may then come at the cost of, e.g., guilt for not living authentically. However, disclosure is a continuum—rather than a dichotomy—meaning that LGB workers may decide to disclose selectively, i.e., telling some, but not all co‐workers. Most literature on disclosure focuses on the interplay between intrapersonal (e.g., psychological) and contextual (e.g., organisational) characteristics, thereby somewhat overlooking the role of interpersonal (e.g., relational) characteristics. In this article, we present findings from semi‐structured, in‐depth interviews with nine Dutch lesbian and gay employees, conducted in early 2020, to gain a better understanding of interpersonal antecedents to disclosure decisions at work. Through our thematic analysis, we find that LGB workers may adopt a proactive or reactive approach to disclosure, which relates to the salience of their sexual identity at work (high/low) and their concern for anticipated acceptance. Other themes facilitating disclosure include an affective dimension, being in a relationship, and associating with the employee resource group. We demonstrate the importance of studying disclosure at the interpersonal level and reflect on how our findings relate to literature on disclosure, authenticity, belonging, and social inclusion of LGB individuals at work.